Strategi Diversifikasi Produk Wisata untuk Menarik Minat Kunjungan Wisatawan di Desa Celuk, Kabupaten Gianyar - Destin, Zilvany; Narottama, Nararya (JURNAL DESTINASI PARIWISATA, 2020)
Celuk Village located in Sukawati, Gianyar, Bali. This village has natural and cultural potencies which can be developed into tourism attractions. For many decades, Celuk is internationally recognized for its silver crafts industries. Unfortunately, since 1998 the tourist visits to this village has been declined, mostly caused by many new competitors in the business. For this reason, this research aims to develop a new strategy to maximize Celuk’s tourism potentials and increase tourists visit. The research approach is qualitative descriptive, the methods such as field observation, in-depth interview with 5 key informants and literature studies. The data analysis using SWOT technique. This research is proposed short-term, mid-term and long-term strategy. Then, based on the result, the best approach is diversification and involvement of local community into all tourism activities. Hopefully, this can make tourism activities in Celuk more diverse and attracts more tourists to come. Keyword: Diversification, Products, Tourism